Terapi Bermain dengan Media Playdough untuk Meningkatkan Motorik Halus pada Anak Usia Pra Sekolah di TK Angkasa Langensari - Sandriani Sandriani; Metty Nurherliyany; Wulan Permatasari; Aditya Nur Wahyuni; Elza Dwi Zuvita; Riza Nuraeni Putri; Rizky Perdana Susanto; Tiara Cahya Rinukti; Andan Firmansyah (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Play therapy is a form of counseling or psychotherapy using games. There are many kinds of game media that train fine motor skills, one of which is assembling the shapes of numbers and letters using playdough media. Playdough media is a toy dough or plasticine toy made of clay (flour), as a learning aid that is easy to shape and very good at training hand and eye coordination in early childhood. Objective: The purpose of this play therapy activity is to improve children's fine motor skills through play therapy using playdough media. Method: This service method is collaborative, with a play therapy approach involving writers and classroom teachers. Data was collected by observing, interviewing, and documenting preschool children in grades A1 and B1 at Angkasa Kindergarten, Langensari District, Banjar City. Result: The results of this activity showed that all participants during the play therapy activity were able to form numbers and letters with their fingers according to the instructions, using playdough media and the children were very enthusiastic and felt happy in doing this play therapy activity. Conclusion: Based on the evaluation of the KPSP questionnaire from this activity, it can be concluded that overall children aged (4-6 years) in TK Angkasa Langensari have fine motor categories that are in accordance with their age development.